Testing an IP-based Multimedia Gateway - Diorio, R. F.; Timóteo, V. S.; Ursini, E. L. (INFOCOMP Journal of Computer Science, 2014)
This paper describes the preliminary results from the development of an IP-based multimedia gateway, using free software resources, to the identification, classification and forwarding of different traffic flows (elastic, more sensitive to packet loss, and stream, more sensitive to communication delays), both with pre-defined traffic profiles. The multimedia gateway performs the traffic selection by inspecting the ToS field of the IPv4 header and the TC field of the IPv6 header, taken as DSCP and ECN. The multimedia traffic corresponding to audio, voice, video and data services are provided by our multimedia traffic generator, which generates traffic according to given distributions. Our tests show that the functional mechanisms of the multimedia gateway are valid and that it can be used as an additional tool for the study and performance evaluation of wireless and wired multimedia networks.